Structural and conformable designs for aqueous multifunctional batteries - Lim, Gwendolyn Jia Hao (2023)
A combination of structural and conformable batteries offers a pathway towards an increased payload capacity and alleviation of ‘range anxiety’ for electric vehicles through effective integration of mechanical stability and energy storage materials. This work focus on a holistic combination of aqueous structural and conformable batteries in vehicles through a multifunctional direct (structural) approach (MFDA) and multifunctional conformable approach (MFCA), applied to the exterior and interior structure of a car, respectively. A highly safe and well-designed aqueous electrolyte composed of Li–Zn hybrid ions was adopted and was well compatible with both the MFDA and MFCA LiMn2O4 cathode system fabricated. A Young's Modulus of 13.57 ± 0.9 GPa for the MFDA cathode was achieved, an order of magnitude higher than conventional slurry coated cathode materials. Additionally, a high rate (5 A/g) capability and superior cycle stability (∼80.3 mAh/g after 1000 cycles @ 2 A/g) of the MFCA batteries with great deformation resilience are also demonstrated. This concept combination was successfully applied in a prototype toy car, and can guide the design of a new generation of structural batteries towards well-distributed energy storage throughout the vehicle.